Factors affecting mortality among victims of electrical burns - Tiryaki, Çağrı; Haksal, Mustafa Celalettin; Yazıcıoğlu, Murat Burç; Çiftçi, Ali; Esen, Osman; Turgut, Hamdi Taner; Yıldırım, Abdullah; Güven, Murat (Turkish Association of Trauma and Emergency Surgery, 2017)
BACKGROUND: The aim of this study was to determine the factors affecting mortality rate among patients with an electrical burn. METHODS: A total of 115 patients admitted to the emergency department and hospitalized in the Burn Treatment Center or Intensive Care Unit (ICU) due to the electrical burn, were included in the study. RESULTS: A total of 115 patients (4 female and 111 male) with a mean age of 32.88 +/- 12.87 years were included in the study. The mean hospitalization period was 25.03 coproduct 20.50 days, and the mean total body surface area burned (% TBSA) was 22.83 +/- 15.54%. Among those patients, 9 (8.5%) expired, and the remaining 106 were discharged after treatment. In a logistic regression analysis, TBSA > 20% (p= 0.02, OR: 11.7, CI: 1.38-99.16); ICU requirement (p= 0.005, OR: 1.28, CI: 1.08-1.58); erythrocyte transfusion requirement (p= 0.02, OR: 12.48, CI: 1.44-107.83); fresh frozen plasma (FFP) requirement (p= 0.03, OR: 10.23, CI: 1.18-88.17); albumin requirement (p= 0.02, OR: 12.60, CI: 1.44-109.85); admission serum albumin level < 3.5 mg/dl (p= 0.04, OR: 7.25, CI: 0.82-63.64); and admission hemoglobin level < 12 mg/dl (p= 0.01, OR: 8.29, CI: 1.57-43.61) were determined as risk factors for mortality in patients with electrical burns. CONCLUSION: In clinical practice, defining a mortality risk analyzer using these factors may be helpful in the management of patients with electrical burns. Additional, more comprehensive studies are required to define the risk factors for mortality and long-term morbidities in patients with electrical burns.

AMAÇ: Bu çalışmanın amacı elektrik yanığı olan hastalarda mortalite oranlarına etki eden faktörleri belirlemektir. GEREÇ VE YÖNTEM: Elektrik yanığı nedeniyle Derince Eğitim ve Araştırma Hastanesi Acil Servisi’ne kabul edilip yanık tedavi merkezi veya yoğun bakıma (YB) yatırılan 115 hasta çalışmaya dahil edildi. BULGULAR: Ortalama yaşı 32.88±12.87 yıl olan toplam 115 hastanın (4 kadın, 111 erkek) çalışmaya alındı. Ortalama hastanede yatış süresi 25.03±20.50 gün ve yanan ortalama toplam vücut yüzey alanı (%TVYA) ise %22.83±15.54 idi. Bu hastaların 106’sı tedavi sonrası taburcu edilirken, dokuzu (%8.5) hayatını kaybetti. Lojistik regresyon analizinde, TVYA >%20 (p=0.02, odds ratio (OR): 11.7, confidence interval (CI): 1.38–99.16), YB gerekenler (p=0.005, OR: 1.28, CI: 1.08–1.58); eritrosit transferi gerekenler (p=0.02, OR: 12.48, CI: 1.44–107.83); Taze donmuş plazma (TDP) gereksinimi olanlar (p=0.03, OR 10.23, CI: 1.18–88.17); albümin gereksinimi olanlar (p=0.02, OR: 12.60, CI: 1.44–109.85); kabulde serum albümin seviyesi <3.5 mg/dL (p=0.04, OR: 7.25, CI: 0.82–63.64); kabul hemoglobin seviyesi <12 mg/dL (p=0.01, OR: 8.29, CI: 1.57–43.61) hastalarda mortaliteyi belirleyen risk faktörleri olarak belirledik. TARTIŞMA: Klinik uygulamada, elektrik yanığı olan hastalarda bu faktörlerin analiz edilmesi mortalite oranını belirlemede yararlı olabilir. Elektrik yanığı olan hastalarda mortalite risk faktörlerini ve uzun dönem morbiditeleri belirlemek için daha geniş çalışmalara gereksinimi vardır.
Elektrik yanıklarında mortaliteye etki eden faktörler
WOS: 000403589400009
PubMed ID: 28530776
Keywords: Albumin; Burn Extent; Calcium; Electrical Burns; Hemoglobin; Mortality; Albümin; Elektrik Yanığı; Hemoglobin; Kalsiyum; Mortalite; Yanık Derecesi